Dietary intake of protein and essential amino acids for sustainable muscle development in elite male athletes - Baranauskas, M.; Kupciunaite, I.; Stukas, R. (Nutrients, 2023)
Athletes need to develop a relatively high muscle mass and low body adipose tissue for the sake of better athletic performance. A full range of nine essential amino acids and eleven non-essential amino acids have to attend in appropriate amounts for protein biosynthesis. The aim of the observational comparative cross-sectional study was to assess the association between the diet quality profile and training-induced muscle mass estimated by bioelectrical impedance among elite male athletes. The research sample comprised 18.1 ± 3.1 year-old Lithuanian professional male athletes (n = 234). The study participants were enrolled to complete 24-h dietary recalls of three non-consecutive days. The body composition was assessed using the bioelectrical impedance analysis (BIA) method. The present study showed a significant insufficiency of the mean carbohydrate intake of 5.7 g/kg/day in a group of aerobic male athletes. The lower muscle mass of aerobic male athletes was related to the lower-carbohydrate diet (adjusted odd ratio (ORadj) 0.3; 95% confidence interval (CI): 0.1-0.7). The mean protein intake of 1.8 g/kg/day was optimal for anabolism in the samples of both anaerobic and aerobic male athletes. The protein intake in appropriate doses was potentially associated with an increase in muscle mass only in anaerobic male athletes (ORadj 2.2; 95% CI: 1.3-3.7). The positive relationship was revealed between the possible muscle mass gain and the increased intakes of amino acids such as isoleucine and histidine among anaerobic athletes (ORadj 2.9; 95% CI: 1.1-4.7 and ORadj 2.9; 95% CI: 1.0-4.3, respectively). An inverse feasible association was indicated between a higher intake of valine and lower muscle mass quantities among anaerobic male athletes (ORadj 0.1; 95% CI: 0.1-0.5). The recommendations for sports nutritionists should emphasize the necessity of advising professional athletes on dietary strategies on how to manipulate dietary amino acid composition with respect to achieving long-term body composition goals.